Java™ Extreme Programming Cookbook - Burke, Eric M. (O'Reilly, 2011)
Brimming with over 100 "recipes" for getting down to business and actually doing XP, the Java Extreme Programming Cookbook doesn't try to "sell" you on XP; it succinctly documents the most important features of popular open source tools for XP in Java-- including Ant, Junit, HttpUnit, Cactus, Tomcat, XDoclet-- and then digs right in, providing recipes for implementing the tools in real-world environments.